Molten salt synthesis and characterization of lead-free (1-x)Na0.5Bi0.5TiO3-xSrTiO3 (x = 0, 0.10, 0.26) whiskers. Issue 8 (1st June 2018) - Zhou, Xuefan; Wu, Zhong; Jiang, Chao; Luo, Hang; Yan, Zhongna; Zhang, Dou
Abstract: In this study, Na0.5 Bi0.5 TiO3 -xSrTiO3 (NBT-xST, x = 0, 0.10, 0.26) whiskers were synthesized by a two step molten salt method using Na2 Ti6 O13 whiskers as templates. The crystalline phase, morphology, microstructure, composition and ferroelectric characteristic of the whiskers were investigated in details. The topochemical transformation from Na2 Ti6 O13 structure to NBT-xST perovskite structure was found to occur by structural rearrangement of the edge sharing octahedra into vertex sharing octahedra. The prepared polycrystalline NBT-xST whiskers possessed high aspect ratio with diameter of 500–800 nm and length of 5–10 µm. The PFM investigations confirmed the favorable piezoelectricity of NBT whiskers while the NBT-0.26ST whiskers displayed relaxor-ferroelectric characteristics at room temperature, exhibiting the potential of NBT-xST whiskers for fabricating high performance micro/nano-devices.